A Versatile Sn‐Substituted Argyrodite Sulfide Electrolyte for All‐Solid‐State Li Metal Batteries. Issue 9 (30th January 2020) - Zhao, Feipeng; Liang, Jianwen; Yu, Chuang; Sun, Qian; Li, Xiaona; Adair, Keegan; Wang, Changhong; Zhao, Yang; Zhang, Shumin; Li, Weihan; Deng, Sixu; Li, Ruying; et al.
Abstract: Sulfide‐based solid‐state electrolytes (SSEs) for all‐solid‐state Li metal batteries (ASSLMBs) are attracting significant attention due to their high ionic conductivity, inherently soft properties, and decent mechanical strength. However, the poor incompatibility with Li metal and air sensitivity have hindered their application. Herein, the Sn (IV) substitution for P (V) in argyrodite sulfide Li6 PS5 I (LPSI) SSEs is reported, in the preparation of novel LPSI‐ x Sn SSEs (where x is the Sn substitution percentage). Appropriate aliovalent element substitutions with larger atomic radius ( R > R ) provides the optimized LPSI‐20Sn electrolyte with a 125 times higher ionic conductivity compared to that of the LPSI electrolyte. The high ionic conductivity of LPSI‐20Sn enables the rich I‐containing electrolyte to serve as a stabilized interlayer against Li metal in sulfide‐based ASSLMBs with outstanding cycling stability and rate capability. Most importantly, benefiting from the strong Sn–S bonding in Sn‐substituted electrolytes, the LPSI‐20Sn electrolyte shows excellent structural stability and improved air stability after exposure to O2 and moisture. The versatile Sn substitution in argyrodite LPSI electrolytes is believed to provide a new and effective strategy to achieve Li metal‐compatible and air‐stable sulfide‐based SSEs for large‐scale applications. Abstract : Partially replacing P with Sn in argyrodite Li6 PS5 I (LPSI) electrolytes can significantly improve the ionic conductivity (125 times higher), Li metal compatibility, and air stability at the same time. This three‐in‐one strategy provides a new idea to alleviate the problems associated with sulfide‐based solid‐state electrolytes.